HAM DAN HUKUMAN MATI MENURUT ATURAN GEREJA KATOLIK: IMPLIKASI PASTORALNYA DI INDONESIA - Yohanes Lon (Unika Santu Paulus Ruteng, 2020)
The enforcement of the death penalty in Indonesia has become a challenge for Indonesian Catholic Church in defending the dignity of human being and his right for life. Through a literature study, this article will highlight the rule of Catholic Church o death penalty and its implications for pastoral activities. The study argues that the dignity of human being is based on its nature as rational, free will and conscience creature. Moreover God has created human beings according to His own image and has redeemed them when destroyed by their own sins. Death penalty is essentially against the dignity of human being and human rights, especially the right to life. Therefore, its enforcement must consider the safety and protection of human rights. The death penalty is only allowed for extraordinary crimes against humanity and is carried out to protect the human rights of others as well as through fair, right and objective justice. The study concludes that in order to protect human rights and the dignity of human being in Indonesia, the Indonesian Catholic Church, through its pastoral works, must promote and defend the noble dignity of human beings and their right to life (pro life pastoral), carry out pastoral of forgiveness and of mercy to the setenced to death, criticize and oversee every trial which results in the death sentence to the defendant (critical prophetic pastoral).